Use of Information Parameters as Criterion for Determination of Biological Activity of Hepatoprotective Preparations - David Areshidze,; Lyudmila Timchenko,; Maria Kozlova,; Igor Rzhepakovsky,; Ivan Syomin, (Journal of Pharmacy and Nutrition Sciences, 2016)
Possibility of use of the information parameters characterizing adaptational and regenerative opportunities of tissue system of an organ as potential criteria for an assessment of biological activity of hepatoprotective preparations is investigated in this research. Influence of enzymatic hydrolyzate of Chlorophytum comosum (L.) on a morphofunctional condition of a liver of rats at experimental toxic damage of organ and in norm was studied. The assessment of morphofunctional condition of a liver under the influence of a preparation was carried out as with use of traditional morphological, biochemical and histologic parameters, and by means of information parameters, which were earlier used for an evaluation of the adaptative and regenerative opportunities of organs of mammals. As a result of research the hepatoprotective effect of enzymatic hydrolyzate of Chlorophytum comosum (L.) is confirmed both by dynamics of change of results of traditional techniques of an assessment and by informational parameters, that allows to draw a conclusion on possibility of use of information parameters as criterion for assesment of effectiveness of biostimulation.